Implementasi Dakwah Fardiyah melalui Bimbingan Ibadah Shalat dalam Mengembangkan Kecerdasan Spiritual Anak Tunadaksa - Permata Sari, Widya; Rojudin, Rojudin; Sabet Rahmawaty, Indira (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
The spiritual condition of disabled children at the Cileunyi State SLB has decreased due to their negligence in performing prayers. Even though the command to pray is obligatory for every Muslim who has reached the age of puberty both in normal conditions and with special needs. So with this prayer guidance is needed in increasing spiritual intelligence. This study aims to determine the concepts, techniques and results of prayer guidance in increasing spiritual intelligence in children with physical disabilities. This study uses qualitative methods. The results of the study show that the concept of prayer guidance carried out there includes preparation before prayer, namely ablution, covering the genitals, determining the place and direction of prayer, and performing the prayer standing and sitting. The prayer guidance technique applied is in the form of repetition and habituation individually and in groups. The results of prayer guidance show cognitive, affective and psychomotor changes, namely: being able to name and distinguish the time and number of cycles of prayer, being able to practice reading and prayer movements, as well as a change in good attitude.